The Effect of Breast Care for Postpartum Mothers on Increasing Breast Milk Production in the Delivery Room of the Sawa Health Center North Konawe Regency - Megi Sukma; Andriyani; Dwi Ayu Rahmawati (Indonesian Journal of Contemporary Multidisciplinary Research, 2023)
This study aims to determine the effect of breast care for postpartum mothers on increasing breast milk production in the delivery room of the Sawa Health Center, North Konawe Regency. This type of research is research using experimental methods with pre and post-test designs. The results showed that the results of the summary of descriptive statistics from both data before and after, the average value for giving treatment before and after has increased from 107,045 to 117,000, where t count is greater than t table (6,913 > 1,6839) with a significant value of 0,000 < α 0.05 which shows that there is an effect, or it can be concluded that through treatment giving treatment can change the amount of milk production where in statistics it is explained that Ha is accepted and H0 is rejected